Postural Tachycardia Syndrome in Children and Adolescents: Pathophysiology and Clinical Management - Chen, Guozhen; Du, Junbao; Jin, Hongfang; Huang, Yaqian (Frontiers in Pediatrics, 2020)
Postural tachycardia syndrome (POTS), characterized by chronic (≥ 6 months) orthostatic intolerance symptoms with a sustained and excessive heart rate increase while standing without postural hypotension, is common in children and adolescents. Despite the unclear pathogenesis of POTS, the present opinion is that POTS is a heterogeneous and multifactorial disorder that includes altered central blood volume, abnormal autonomic reflexes, “hyperadrenergic” status, damaged skeletal muscle pump activity, abnormal local vascular tension and vasoactive factor release, mast cell activation, iron insufficiency, and autoimmune dysfunction. A number of pediatric POTS patients are affected by more than one of these pathophysiological mechanisms. Therefore, individualized treatment strategies are initiated in the management of POTS, including basal nonpharmacological approaches (e.g., health education, the avoidance of triggers, exercise, or supplementation with water and salt) and special pharmacological therapies (e.g., oral rehydration salts, midodrine hydrochloride, and metoprolol). As such, the recent progress in the pathogenesis, management strategies and therapeutic response predictors of pediatric POTS are reviewed here.